Strategi Komunikasi Nahdlatul Ulama Dalam Meningkatkan Eksistensinya Sebagai Organisasi Kemasyarakatan Berbasis Islam Pengikut Ajaran Hadratus Syeikh Hasyim Ashari - Awan Dharmawan; Titi Stiawati; Ipah Ema Jumiati; Ayununing Budiati (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This study aims to analyze how the Communication Strategy carried out by Nahdlatul Ulama as an Islamic-based Community Organization Followers of the Teachings of Hadratus Syeikh Hasyim Ashari in increasing its existence. In this research a qualitative descriptive approach was used. Solving problems related to strategy is by using the SWOT Analysis Approach. Observations were carried out by conducting interviews with 4 informants who knew the problem. From the observations made, all of them show that the Communication Strategy carried out by Nahdlatul Ulama as an Islamic-based Community Organization Followers of the Teachings of Hadratus Syeikh Hasyim Ashari Service by attaching photos or pictures of Hadratus Syeikh Hasyim Ashari on billboards, banners and flyers for various kinds of events, is a strategy that effective according to the expected goals and in accordance with the function and theory of communication.